DETERMINANTS OF FINANCIAL PERFORMANCE IN REGIONAL DEVELOPMENT BANKS ON THE ISLANDS OF BORNEO AND JAVA - Ana Dwi Pertiwi (International Journal Management and Economic, 2025)
Regional Development Banks are currently faced with increasing demands to adapt and advance given rapid technological innovations, ever-changing market conditions, and increasing competition within the financial services sector. The sample examined in this study consists of ten BPD institutions located on the islands of Kalimantan and Java, selected through purposive sampling methodology. The variables analyzed in this study include NPL, CAR, and BOPO as independent variables, with ROA set as the dependent variable. The analytical techniques used include simple regression analysis as well as multiple regression analysis, using SPSS, Version 26. The findings of this study indicate that the NPL, CAR, and LDR variables exert a significant influence on the ROA ratio of BPD institutions located on the islands of Kalimantan and Java during the period 2019 to 2023, both partially and simultaneously.